Manajemen Kebijakan SPMI dalam Meningkatkan Kinerja Sekolah di SMK: (Studi kasus di SMK Bina Teknologi Subang dan SMK Al-Multi Purwadadi) - Yogi Sugiyana (Simpati, 2025)
The Internal Quality Assurance System (SPMI) is a strategic mechanism for directing and controlling the quality of education through continuous planning, implementation, evaluation, and follow-up processes. This study aims to describe and analyze the management of SPMI in improving the performance of Vocational High Schools (SMK), with research sites at SMK Bina Teknologi Subang and SMK Al-Mufti Purwadadi. Using a descriptive qualitative approach, this study examines the implementation of management functions based on the PDCA (Plan, Do, Check, Action) cycle within the context of educational quality assurance. The results indicate that the implementation of SPMI contributes positively to improving school performance, particularly in meeting and exceeding the National Education Standards (SNP), as reflected in the school self-evaluation results and recommendations in the education report card. Furthermore, the implementation of SPMI encourages schools to carry out root-cause-based improvements through systematic program planning, activity development, and priority setting. These findings highlight that the success of SPMI is strongly influenced by consistent implementation and the commitment of all school stakeholders. The Novelty of this study lies in the development of a hypothetical SPMI model based on performance management, which is relevant for enhancing the quality and competitiveness of vocational schools in a sustainable manner.